Education in rural America are we doing the job - Isenberg, Robert M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
Although rural education has many advantages, American rural school systems are not capitalizing upon the opportunities afforded them. While many rural schools have not kept up with the changes that have occurred in the past two decades, most do have libraries and laboratories. However, the majority is not served by specialized classes in vocational and technical education, programs for blind or deaf students, learning centers, or teachers who are inquisitive enough to explore new and different instructional approaches to provide more meaningful educational experiences. Many times rural areas do not benefit from high quality teachers because these teachers are lured away by more desirable wages and living conditions in urban areas. All of these reasons, plus the fact that most rural schools do not have a kindergarten program, lead to rural students' dropping out of school at an early age. Consequently, rural youth are not being prepared to meet the demands of their future environments. This paper was presented at the national outlook conference on rural youth, October 24, 1967, Washington, D. C., sponsored jointly by the U. S. Departments of agriculture, health, education, and welfare, interior, and labor, oeo, and the president's council on youth opportunity. (cl)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Educational Change; Educational Facilities; Educational Programs; Rural Education; Rural Schools; School Districts; Teacher Employment; Teacher Shortage; Teachers